(untitled) (Research, Society and Development, 2024)
Introduction: Aesthetics as an area within Dentistry has become fundamental, making it necessary to acquire knowledge beyond oral health, in order to promote confidence, self-esteem and well-being in patients, directly reflecting on their quality of life. The objective of this article is to present a study on enamel hypoplasia. Methodology: This article addresses dental enamel hypoplasia through a narrative review of the literature. Conclusion: Continuous advancement in knowledge and clinical techniques is crucial to improve the understanding, diagnosis and treatment of this condition, thus promoting better oral health for patients.